Design of linear and nonlinear controller for DC-DC boost converter with right-half plane zero. (16th December 2021) - Anitha, T.; Arulselvi, S.
A major problem arises in the controller design when the transfer function of control-to-output voltage has right-half plane (RHP) zero. The effect of RHP zero predominates in the transfer functions of boost and buck-boost converters leading to a tedious controller design. Hence in this paper, the design of linear and nonlinear controllers for a DC-DC boost converter is discussed. Since the design of the linear controller (PI) strongly depends on the small signal transfer function of the converters, it leads to poor voltage regulation for wide variation in operating point. To overcome the above said difficulties and to achieve large signal stability, robustness, good dynamic response and simple implementation, an additional inner loop employing sliding mode control (SMC) with boundary layer is proposed in current mode control (CMC) scheme. Extensive simulation studies are carried out for DC-DC boost converter with RHP zero to verify the merits of SMC over PI controller using MATLAB/Simulink software.